RELEVANCE OF ISLAMIC BANKING IN INDONESIA TO THE MUAMALAH SYSTEM OF THE PROPHET AND THE CALIPH - Anantyasari, Malta; Suwarno, Agus Endro; Nashirudin, Muh.; Mu’awanah, Chabibatul; Asri, Nuraini Binti (Journal of Islamic Economic Laws, 2022)
The emergence of Islamic banks in Indonesia today is increasingly mushrooming. This emergence is inseparable from the role of the number of Muslim populations in Indonesia who want an Islamic economic and banking system that is far from usury. The Islamic banking system has been exemplified by the Prophet Muhammad and his companions in the past. His companions have become the basis or foundation for establishing Islamic banks. However, in reality, in Indonesia, the relevance of the Islamic banking system is less attractive. This research is descriptive qualitative research, using the library research method. This study aims to examine the practice of Islamic banking as exemplified at the time of the Prophet Muhammad SAW and to see the relevance and development of Islamic banking practices in Indonesia. This study concludes that the model of banking services, products, and activities exemplified by the Prophet is still used in the Islamic banking system in Indonesia. However, many Islamic bank practices deviate and are not by Sharia rules.